Virus-like particles in a new vaccination approach against infectious laryngotracheitis. (17th May 2019) - Schädler, Julia; Sigrist, Brigitte; Meier, Simone M.; Albini, Sarah; Wolfrum, Nina
Abstract : Gallid alphaherpesvirus 1 (syn. infectious laryngotracheitis virus; ILTV) is the causative agent of infectious laryngotracheitis, a respiratory disease of chickens causing substantial economic losses in the poultry industry every year. Currently, the most efficient way to achieve protection against infection is immunization with live-attenuated vaccines. However, this vaccination strategy entails the risk of generating new pathogenic viruses resulting from spontaneous mutations or from recombination with field strains. This work presents a new approach based on virus-like particles (VLPs) displaying ILTV glycoproteins B (gB) or G (gG) on their surface. The main focus of this pilot study was to determine the tolerability of VLPs delivered in ovo and intramuscularly (i.m.) into chickens and to investigate the nature of the immune response elicited. The study revealed that the new vaccines were well tolerated in hybrid layer chicks independent of the administration method ( in ovo or i.m.). Upon in ovo injection, vaccination with VLP-gG led to an antibody response, while a cellular immune response in VLP-gB-immunized chickens was hardly detectable. Since the administration of VLPs had no visible side effects in vivo and was shown to elicit an antibody-based immune response, we anticipate that VLPs will become a valuable platform for the development of new safe vaccines for poultry.